First results and experience with PRRT in South Africa - Vorster, Mariza; Modiselle, M; Corbett, C; Lawal, I; Buscombe, John; Sathekge, Mike (World Journal of Nuclear Medicine, 2018)
Neuroendocrine tumors (NETs) are a diverse group of tumors that often present late due to nonspecific symptoms. These tumors frequently express somatostatin receptors (SSRs), which allows for positron emission tomography/computed tomography (PET/CT) imaging with Ga-68-DOTATATE. In eligible patients, this may then be followed by peptide receptor radionuclide therapy (PRRT). Here, we report our initial results and experience with PRRT in a developing country, as one of the first groups to provide this therapy in South Africa. Eligible patients with confirmed inoperable NETs were recruited prospectively and treated with Lu-177-DOTATATE. Baseline imaging was performed with either single-photon emission CT- or PET-based SSR analogs, whereas follow-up was performed with 68Ga-DOTATATE PET/CT 6 months post treatment completion. Interim treatment response evaluation was based on post therapy imaging of Lu-177-DOTATATE. A total of 48 patients with a mean age of 58 years were treated with PRRT, of whom 22 (46%) demonstrated stable disease, 20 (42%) demonstrated a partial response, and 6 (12%) demonstrated progressive disease. The median progression-free survival (PFS) was 20 months with an interquartile range (IQR)25%–75%of 4.5–30 months. The median freedom from progression duration was 32 months with an IQR25%–75%of 25–40 months, and the median overall survival was 10 months with an (IQR)25%–75%of 5–24 months. Our subgroup analysis demonstrated an inverse association between metabolic tumor volume with PFS, which requires further validation. In conclusion, PRRT with Lu-177-DOTATATE resulted in a median PFS of 20 months in patients with inoperable NETs in the absence of significant side effects.
Keywords: LuTate; neuroendocrine tumors; PRRT